PERLAWANAN ALAM TERHADAP KOLONIALISME DALAM NOVEL POHON JEJAWI KARYA BUDI DARMA - Maimunah Maimunah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe: (1) how colonial ecocriticism is represented, and (2) whattext ideologies are like. The short story Pohon Jejawi presents a Dutch colonial setting inSurabaya in the 1930s. The main character was Henry van Kopperlink, a new mayor ofSurabaya, who felt disturbed by the existence of a jejawi tree, which was full of mysticalmyth and mystery. The mystical old tree growing in Kedung Gang Buntu was unable to bechopped down several times because the birds hiding in its dense leaves made every effortto cut it down fail. Using the green studies perspective, this short story presents colonialmasculinity represented the main characters; it is unable to be established in Surabaya.The tropical nature represented by the jejawi tree is capable of making the colonial rusten orde chaotic. In Pohon Jejawi, Budi Darma tells that colonialism is opposed not only bythe indigenous West Indie people but also by the mysticism of the jejawi tree.